Cross–Cultural Research: Adaptation and Validation of Emotional Development Questionnaire for Adults (QDE_A) - Silva, Maria do Carmo (2012)
All organizations target a leading position in the market they operate in. To attain this leading position, it is essential to correctly balance the associates’ rational and emotional competences. Hence the pertinence of instruments which allow the measurement of the associates’ level of emotional competences. This paper describes the process that this specific method adopted in the cross-cultural translation of QDE_A (Questionnaire: Emotional Development for Adults) – the Spanish version into Portuguese (European) language. Our results allowed us to provide a tool in Portuguese language to evaluate emotional competences useful for human resources’ managers as well as coaches